Indonesia Gender and Environmental Empowerment Contour: An Ecofeminist Approach to Joko Widodo’s Development Model - Anwar, Muhammad Ikhwan Nuril (Institute of International Studies, 2025)
This paper examines the contour of Indonesia’s development under President Joko Widodo, focusing on three prominent megaprojects: the Ibu Kota Nusantara (IKN) new capital city project, nickel industry downstreaming, and the Food Estate program. Using an ecofeminist framework developed from previous key literature, this study assesses these projects through the lenses of inclusive participation and indigenous integration, sustainability, and environmental justice. Ecofeminism critiques development models that prioritize economic growth over ecological and social well-being, often at the expense of marginalized communities and the environment. This research adopts a qualitative approach, relying on internet-based data collection from official statements, media sources, and relevant academic articles. The findings reveal that, while these projects are framed as drivers of economic progress, they frequently sideline local communities, overlook sustainable practices, and worsen environmental inequalities. The study highlights the lack of indigenous participation and the uneven distribution of benefits and burdens, reinforcing the need for a more just and inclusive approach to development in Indonesia. This analysis addresses a gap in previous studies on Indonesian development, which have seldom applied a macroscopic ecofeminist perspective to Jokowi’s policies. The findings therefore suggest the importance of integrating local knowledge and sustainable practices in future and existing development endeavors.